The Physicochemical and Antimicrobial Properties of Silver/Gold Nanoparticles Obtained by "Green Synthesis" from Willow Bark and Their Formulations as Potential Innovative Pharmaceutical Substances - Roxana Colette Sandulovici; Mihailescu Carmen-Marinela; Alexandru Grigoroiu; Carmen Aura Moldovan; Mihaela Savin; Viorel Ordeanu; Sorina Nicoleta Voicu; Daniel Cord; Gabriela Mariana Costache; Mona Luciana Galatanu; Mariana Popescu; Iulian Sarbu; et al. (MDPI AG, 2022)
Green chemistry is a pharmaceutical industry tool, which, when implemented correctly, can lead to a minimization in resource consumption and waste. An aqueous extract of Salix alba L. was employed for the efficient and rapid synthesis of silver/gold particle nanostructures via an inexpensive, nontoxic and eco-friendly procedure. The nanoparticles were physicochemically characterized using ultraviolet-visible spectroscopy (UV-Vis), Fourier transform infrared spectroscopy (FT-IR), dynamic light scattering (DLS), X-ray diffraction (XRD) and scanning electron microscopy (SEM), with the best stability of up to one year in the solution obtained for silver nanoparticles without any chemical additives. A comparison of the antimicrobial effect of silver/gold nanoparticles and their formulations (hydrogels, ointments, aqueous solutions) showed that both metallic nanoparticles have antibacterial and antibiofilm effects, with silver-based hydrogels having particularly high antibiofilm efficiency. The highest antibacterial and antibiofilm efficacies were obtained against Pseudomonas aeruginosa when using silver nanoparticle hydrogels, with antibiofilm efficacies of over 75% registered. The hydrogels incorporating green nanoparticles displayed a 200% increased bacterial efficiency when compared to the controls and their components. All silver nanoparticle formulations were ecologically obtained by "green synthesis" and were shown to have an antimicrobial effect or potential as keratinocyte-acting pharmaceutical substances for ameliorating infectious psoriasis wounds.